The Mediating Role of Sustainable Leadership in Green Human Resource Management Practices and Organizational Commitment: A Case Study in Turkey - Hatipoğlu, Zeynep; Akduman, Gülbeniz (Sustainability, 2025)
Today, businesses operate to maintain their assets sustainably and profitably, but they face resource scarcity and environmental problems. In order to overcome this problem, businesses should focus on environmental, social, and economic development while considering the environment. In this context, green human resource practices and sustainable leadership, which have emerged from green management philosophy, increase the environmental awareness of businesses and support them in protecting resources while also positively affecting many human resource metrics, such as performance and commitment at the business level. In recent years, definitions have been established, and scales have been developed within the scope of green human resource and sustainability leadership research, which has been a subject of interest in the relevant literature. Because studies measuring the effects of green human resource management (HRM) and sustainable leadership at the business level are rare, this work is important as it provides resources for further research. In this context, this research aimed to analyze the effects of green human resource management practices and sustainable leadership on employee commitment. In order to reach a general judgment about a system consisting of a large number of people and find answers to the research questions, the general screening model, which allows for single or relational screenings over the entire system or a group of samples to be taken from it, was selected. The correlational model, a type of quantitative research model, was used to examine the relationships between the variables within the scope of this research. According to the results, the effects of green HRM practices on organizational commitment change significantly through the mediation of sustainable leadership. The findings reveal that, for organizations seeking to foster a sustainable business culture, merely implementing green policies is insufficient; leaders must also embody these practices and motivate their workforce. Such an integrated strategy enhances both ecological sustainability and employee commitment, thereby securing a lasting competitive edge.